Evaluation of Serum Procalcitonin and C-Reactive Protein as Early Biomarkers of Surgical Site Infections in Head and Neck Surgical Patients - Muhammad Farooq Bhutta, Inamullah, Muhammad Firdous, Abrar-Ul-Hassan Pirzada, Habib Ullah, Saher Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical site infections (SSIs) are among the most common postoperative complications following head and neck surgeries and are associated with increased morbidity, prolonged hospital stay, and higher healthcare costs. Early identification of infection is important to improve patient outcomes. Serum biomarkers such as procalcitonin (PCT) and C-reactive protein (CRP) have been proposed as useful indicators for early detection of postoperative infections. Objective: To evaluate the role of serum procalcitonin and C-reactive protein in predicting surgical site infections in patients undergoing head and neck surgeries. Methods: This prospective observational study was conducted at the Department of Otorhinolaryngology (ENT), Shahida Islam Medical College and Teaching Hospital, Lodhran, Pakistan, from February 2022 to February 2023. A total of 100 patients undergoing elective head and neck surgeries were included. Serum procalcitonin and C-reactive protein levels were measured preoperatively and postoperatively. Patients were followed for 30 days after surgery for the development of surgical site infections based on clinical assessment and CDC criteria. Statistical analysis was performed using SPSS version 25. Results: Out of 100 patients, 22% developed surgical site infection during the postoperative follow-up period. Patients with SSI showed significantly higher postoperative levels of procalcitonin and C-reactive protein compared with those without infection (p < 0.001). Procalcitonin demonstrated higher specificity (89%) for detecting bacterial infection, whereas CRP showed higher sensitivity (87%) for postoperative inflammatory response. Conclusion: Serum procalcitonin and C-reactive protein are useful biomarkers for predicting surgical site infections after head and neck surgeries. Monitoring these markers in the postoperative period may facilitate early detection and timely management of infection. Keywords: Surgical site infection, Procalcitonin, C-reactive protein, Head and neck surgery, Biomarkers, Postoperative infection.